2008
DOI: 10.1080/09537100701230451
|View full text |Cite
|
Sign up to set email alerts
|

The association of mean platelet volume levels with hypertensive retinopathy

Abstract: The pathophysiological mechanism of hypertensive retinopathy (HR) is not fully established. Elevated blood pressure alone does not fully account for the extent of retinopathy so other pathogenic mechanisms may be involved, such as increased platelet activation. Mean platelet volume (MPV) is a marker of platelet activation. Therefore, this study was designed to answer the following questions: Do MPV levels change in HR? and is there any relation between degree of HR and MPV levels? This study included newly dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“…Whereas the cell differentials and platelet counts were in the normal range (290,000 to 650,000 platelets/μl) for rabbits immunized with the MAP-19mer (Penelope and Patricia), rabbits immunized with the MAP-14mer had low or borderline low normal platelet counts of 187,000/μl (Alice) and 290,000/μl (Rosita) after the third boost, which remained below normal (250,000/μl) in only one rabbit (Alice) at bleed-5; however, none of the rabbits were anemic. The mean platelet volume (MPV) was 3–fold higher in the rabbit with the lowest platelet counts (Alice), which is consistent with platelet activation and platelet destruction (immune thrombocytopenia) and new platelet production (Coban et al, 2008). Adherence of platelets on neutrophils and monocytes, known as satellitism, was observed (not shown), which is frequently associated with sporadic thrombocytopenia (Lazo-Langner et al, 2002).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Whereas the cell differentials and platelet counts were in the normal range (290,000 to 650,000 platelets/μl) for rabbits immunized with the MAP-19mer (Penelope and Patricia), rabbits immunized with the MAP-14mer had low or borderline low normal platelet counts of 187,000/μl (Alice) and 290,000/μl (Rosita) after the third boost, which remained below normal (250,000/μl) in only one rabbit (Alice) at bleed-5; however, none of the rabbits were anemic. The mean platelet volume (MPV) was 3–fold higher in the rabbit with the lowest platelet counts (Alice), which is consistent with platelet activation and platelet destruction (immune thrombocytopenia) and new platelet production (Coban et al, 2008). Adherence of platelets on neutrophils and monocytes, known as satellitism, was observed (not shown), which is frequently associated with sporadic thrombocytopenia (Lazo-Langner et al, 2002).…”
Section: Resultssupporting
confidence: 58%
“…Platelet depletion and increased MPV reflect the state of thrombogenesis (Hekimsoy et al, 2004). High MPV is associated with low platelet counts due to platelet destruction (immune thrombocytopenia) and platelet activation (Coban et al, 2008, Sullivan et al, 1995). Increase in MPV occurs in patients with metabolic syndrome, stroke and diabetes mellitus (Zuberi et al, 2008), contributing to the increased vascular complications and endothelial cell dysfunction observed (Hekimsoy et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These findings concur with the result of a previous study. 8 Thus, it is a highly relevant finding that MPV in patients with hypertension is significantly higher than in normotensive control subjects. 9 There is growing evidence that increased platelet activation, a common finding in hypertension, may contribute significantly to these complications with serious vascular atheroscerotic diseases, such as stroke, coronary artery disease, and retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…7 The literature on the association between MPV and stroke is inconsistent 8,9 and may also relate to the use of different methods to assess MPV and the variable time points used for MPV measurement after stroke onset. 10 Moreover, emerging evidence has shown that known cardiovascular risk factors, such as smoking, 11 diabetes mellitus, 12 obesity 13 and hypertension, 14,15 are associated with MPV. Prehypertension, as defined by the Seventh Joint National Committee, 16 includes those with systolic blood pressure ranging 120-139 mm Hg or diastolic blood pressure ranging 80-89 mm Hg, is identified as a predictor for developing hypertension 17 and a stage where the primary prevention of hypertension is possible.…”
Section: Introductionmentioning
confidence: 99%